Two girls want a puppy - Cordell, Ryan; Cordell, Evie (Harper, an imprint of HarperCollinsPublishers, 2015)
Two sisters, Cadence and Emi, show great persistence and ingenuity in trying to persuade their father that they're ready to adopt a puppy.